PENGEMBANGAN MANAJEMEN KAWASAN EKOWISATA BUDAYA CANDI MUARA TAKUS KAMPAR RIAU - Sukma, Dodi; Basuni, sambas; Sunarminto, Tutut (Media Konservasi, 2016)
Muara Takus Temple (MTT) is a relic of the kingdom of Sriwijaya derived from Buddhism and it has the potential to be developed as a tourist attraction. MTT cultural development of the ecotourism area as a cultural heritage, tourist destinations and places of worship need to be done as a measure to keep the MTT area and improve the local economy. If cultural tourism will be managed carefully, it will be had the economic potential as the motivation for the cultural stakeholders to provide rewards and protection of cultural heritage. In other words, cultural tourism has a double significance that is able to increase the economic value and cultural value. The research aimed to develop ecotourism management of cultural MTT. The used method was the method of survey (survey methods) with a questionnaire technique, which was a collection of data that provided a list of questions/statements to the informant/respondent hoped of providing a response to the questionnaire. The used questionnaire was elaborated from the combination question/statement patterned open, closed and scale (rating). The research showed that the parties were supported the development of management area eco-cultural tourism muara takus temple. Eliminating the gaps by establishing an agency has been to manage the MTT in order to avoid overlapping policies and has been facilitated communication, coordination, collaboration parties were involved to achieve the desired objectives.  Keywords: eco-cultural tourism, immaterial, material, muara takus temple